Disengagement From HIV Care and Failure of Second-Line Therapy in Nigeria: A Retrospective Cohort Study, 2005–2017. (1st May 2022) - El Bouzidi, Kate; Murtala-Ibrahim, Fati; Kwaghe, Vivian; Datir, Rawlings P.; Ogbanufe, Obinna; Crowell, Trevor A.; Charurat, Man; Dakum, Patrick; Gupta, Ravindra K.; Ndembi, Nicaise; Sabin, Caroline A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Understanding the correlates of disengagement from HIV care and treatment failure during second-line antiretroviral therapy (ART) could inform interventions to improve clinical outcomes among people living with HIV (PLHIV). Methods: We conducted a retrospective cohort study of PLHIV aged >15 years who started second-line ART at a tertiary center in Nigeria between 2005 and 2017. Participants were considered to have disengaged from care if they had not returned within a year after each clinic visit. Cox proportional hazard models were used to investigate factors associated with: (1) viral failure (HIV-1 RNA >1000 copies/mL), (2) immunologic failure (CD4 count decrease or <100 cells/mm 3 ), and (3) severe weight loss (>10% of bodyweight), after >6 months of second-line ART. Results: Among 1031 participants, 33% (341) disengaged from care during a median follow-up of 6.9 years (interquartile range 3.7–8.5). Of these, 26% (89/341) subsequently reentered care. Disengagement was associated with male gender, age <30 years, lower education level, and low CD4 count at second-line ART initiation. Among participants with endpoint assessments available, 20% (112/565) experienced viral failure, 32% (257/809) experienced immunologic failure, and 23% (190/831) experienced weight loss. A lower risk of viral failure was associated with professional occupations compared with elementary: adjusted hazard ratio 0.17 (95% confidence interval 0.04 to 0.70). Conclusion: Adverse outcomes were common during second-line ART. However, reengagement is possible and resources should be allocated to focus on retaining PLHIV in care and providing services to trace and reengage those who have disengaged from care.